Distributional responses to marine heat waves: insights from length frequencies across the geographic range of the endemic reef fish Choerodon rubescens - Cure, K.; Hobbs, J.; Langlois, T.; Abdo, D.; Bennett, Scott; Harvey, E. (Springer-Verlag, 2018)
© 2017, Springer-Verlag GmbH Germany. Range shifts as a result of warming oceans call for evaluation of populations at the geographic range level, particularly for highly vulnerable species such as endemics and fisheries targets. We examined the influence of latitudinal temperature gradients and temperature anomalies during a 2011 marine heat wave on range-wide abundance, length frequency and recruitment of Choerodon rubescens, a reef associated fisheries target endemic to Western Australia. Diver-operated stereo-video surveys were conducted at shallow reefs (3–18 m) along 124 sites spanning the entire species’ distribution (21°S–34°S), to obtain abundance, length frequency and habitat data. Models were used to assess the influence of satellite-derived long-term average temperature (2002–2010) and 2011 temperature anomalies, compared to habitat, depth and distance to mainland, on the abundance of adult and juvenile fish and overall population size structure. Long-term temperature had the highest effect on adult C. rubescens abundance, with highest values recorded towards the centre of the temperature gradient investigated (22 °C). In contrast, juveniles were mostly influenced by 2011 temperature anomalies, with highest abundance recorded towards the cooler range edge, where anomalies were lowest. Length-frequency distributions showed recent recruitment towards the cooler range edge coupled with recruitment absence at the warmer edge. Recruitment differences were traced to 2011–2013 when ocean temperatures were up to 3.5 °C higher than average, via back-calculation of juvenile ages. These findings support predictions of a poleward distributional shift in response to ocean warming, and suggest that marine heatwaves can facilitate range shifts by affecting recruitment across latitudinal gradients.